Coral microbiome diversity reflects mass coral bleaching susceptibility during the 2016 El Niño heat wave - Stephanie G. Gardner (Ecology and Evolution, 2019)
Abstract Repeat marine heat wave‐induced mass coral bleaching has decimated reefs in Seychelles for 35 years, but how coral‐associated microbial diversity (microalgal endosymbionts of the family Symbiodiniaceae and bacterial communities) potentially underpins broad‐scale bleaching dynamics remains unknown. We assessed microbiome composition during the 2016 heat wave peak at two contrasting reef sites (clear vs. turbid) in Seychelles, for key coral species considered bleaching sensitive (Acropora muricata, Acropora gemmifera) or tolerant (Porites lutea, Coelastrea aspera). For all species and sites, we sampled bleached versus unbleached colonies to examine how microbiomes align with heat stress susceptibility. Over 30% of all corals bleached in 2016, half of which were from Acropora sp. and Pocillopora sp. mass bleaching that largely transitioned to mortality by 2017. Symbiodiniaceae ITS2‐sequencing revealed that the two Acropora sp. and P. lutea generally associated with C3z/C3 and C15 types, respectively, whereas C. aspera exhibited a plastic association with multiple D types and two C3z types. 16S rRNA gene sequencing revealed that bacterial communities were coral host‐specific, largely through differences in the most abundant families, Hahellaceae (comprising Endozoicomonas), Rhodospirillaceae, and Rhodobacteraceae. Both Acropora sp. exhibited lower bacterial diversity, species richness, and community evenness compared to more bleaching‐resistant P. lutea and C. aspera. Different bleaching susceptibility among coral species was thus consistent with distinct microbiome community profiles. These profiles were conserved across bleached and unbleached colonies of all coral species. As this pattern could also reflect a parallel response of the microbiome to environmental changes, the detailed functional associations will need to be determined in future studies. Further understanding such microbiome‐environmental interactions is likely critical to target more effective management within oceanically isolated reefs of Seychelles.